2018
DOI: 10.1021/acs.bioconjchem.8b00452
|View full text |Cite
|
Sign up to set email alerts
|

Mercaptopyrimidine-Conjugated Gold Nanoclusters as Nanoantibiotics for Combating Multidrug-Resistant Superbugs

Abstract: Widespread bacterial resistance induced by the abuse of antibiotics eagerly needs the exploitation of novel antimicrobial agents and strategies. Gold nanoclusters (Au NCs) have recently emerged as an innovative nanomedicine, but study on their antibacterial properties especially toward multidrug resistant (MDR) bacteria is scarce. Herein, we demonstrate that a novel class of Au NCs, mercaptopyrimidine conjugated Au NCs, can act as potent nanoantibiotics targeting these intractable superbugs in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 48 publications
0
69
0
Order By: Relevance
“…The total antibacterial activity is mainly attributed to the synergistic effect of SFT and NDs on the disruption of the bacterial cell membrane. In our recent study, we developed an effective antibacterial hybrid (Dap-Au NCs) by incorporating antimicrobial peptide (daptomycin, Dap) and antibacterial Au NCs (Zheng et al, 2018c;. The antibacterial hybrid could high-efficiently damage bacterial cell membrane because Dap moiety may induce the creation of holes on the cell membranes, and motivate the entry of Dap-Au NCs inside bacteria and even lead to serious DNA destruction (Figure 7A).…”
Section: Antimicrobial Peptide-au Ncs Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total antibacterial activity is mainly attributed to the synergistic effect of SFT and NDs on the disruption of the bacterial cell membrane. In our recent study, we developed an effective antibacterial hybrid (Dap-Au NCs) by incorporating antimicrobial peptide (daptomycin, Dap) and antibacterial Au NCs (Zheng et al, 2018c;. The antibacterial hybrid could high-efficiently damage bacterial cell membrane because Dap moiety may induce the creation of holes on the cell membranes, and motivate the entry of Dap-Au NCs inside bacteria and even lead to serious DNA destruction (Figure 7A).…”
Section: Antimicrobial Peptide-au Ncs Systemsmentioning
confidence: 99%
“…Similar circumstances have been witnessed in our recent work. We demonstrated that mercaptopyrimidine analogs templated Au NCs can serve as potent nanoantibiotics for ESKAPE superbugs (Zheng et al, 2018c). Mercaptopyrimidine analogs, including 4,6-dihydroxyl-2-mercaptopyrimidine (DHMP), 4-amino-6-hydroxyl-2-mercaptopyrimidine (AHMP), 4,6-diamino-2-mercaptopyrimidine (DAMP), and 4-amino-2-mercaptopyrimidine (AMP), were employed as templates and reducing agents to prepare Au NCs.…”
Section: Small Molecule-au Ncs Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AuNPs do not exhibit antibacterial property, but due to the presence of unreacted ligands or some ionic impurities, they act as an antibacterial agent . AuNPs can be made antibacterial by grafting hydrophobic molecules, antibacterial peptides, antibiotics and a molecule which makes the gold nanoparticles positively charged . Most often, antibiotic molecules have been used to make the AuNPs antibacterial in nature .…”
Section: Gold Nanoparticles and Their Antibacterial Applicationsmentioning
confidence: 99%
“…Thus, 4, 6-diamino-2-mercaptopyrimidine (DAMP), an analog of 2-mercaptopyrimidine in the tRNA of E. coli, has been employed as the surface ligand to functionalize AuNCs. The DAMP-capped AuNCs show a robust capacity to eliminate bacteria through DNA destruction, membrane damage, and ROS production (Zheng et al, 2018). Importantly, the AuNCs have great biocompatibility and antibacterial efficiency, indicating that they are suitable for clinical infection therapy.…”
Section: Introductionmentioning
confidence: 99%